Penerapan Metode Brainstorming dalam Meningkatkan Pemahaman Peserta Didik pada Mata Pelajaran Fiqih di Madrasah Aliyah Al-I'dadiyyah Bahrul Ulum Tambakberas Jombang - Nisa’, Khoirun; Wahyudi, Wahyudi; Choir, Miftachul (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Fiqh lessons are integrated between the life of the world and the hereafter. This study aims to determine the understanding of improvement, supporting factors and inhibiting factors of fiqh using the Brainstorming method at Madrasah Aliyah Al I'dadiyyah Bahrul Ulum Tambakberas Jombang. This research is a descriptive qualitative research. To obtain the data needed in research, researchers used observation, interviews, and documentation. The results of the research on the Brainstorming method are effective in teaching and learning activities because they are able to increase deep understanding and memory of the material that has been studied, because they are active in voicing opinions. Between listening and speaking, students will understand better by expressing their own opinions, because it is in accordance with the thoughts of each student. The advantages of Brainstorming are being able to make students more active in expressing their opinions according to what they understand, while the disadvantages of students in this method are that they do not immediately know whether their opinion is right or wrong. Then the increase in students' understanding of fiqh subjects in the Brainstorming method can be seen from the results of distributing questionnaires to students, and based on the results that the average student is able to apply the Brainstorming method to fiqh subjects, because the Brainstorming method helps students to easily absorb subjects.